Improving transitions in care for children and youth with mental health concerns: implementation and evaluation of an emergency department mental health clinical pathway - Tucci, Alexandra; Cloutier, Paula; Polihronis, Christine; Kennedy, Allison; Zemek, Roger; Gray, Clare; Reid, Sarah; Pajer, Kathleen; Gardner, William; Barrowman, Nicholas; Cappelli, Mario; Jabbour, Mona (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Emergency departments (EDs) are often the first access point for children and youth seeking mental health (MH) and addiction care. However, many EDs are unprepared to manage large volumes of pediatric MH patients. In addition, the fragmented Canadian MH system is challenged in connecting youth seen in the ED for follow-up community services. A provincial Emergency Department Mental Health Clinical Pathway (EDMHCP) for children and youth presenting to the ED with MH concerns was developed to address these challenges. The objective of the current study was to determine if EDMHCP implementation resulted in: (1) pathway use, (2) more patients discharged with MH recommendations, (3) MH service recommendations that aligned with patients’ risk assessments, and (4) changes in service outcomes, including ED length of stay (LOS), revisits, and admissions/transfers. Methods We implemented the pathway at four ED sites from 2018 to 2019 using the Theoretical Domains Framework to develop a tailored strategy at each site. We conducted chart reviews retrospectively in 2017–2018 (pre-implementation) and prospectively in 2019–2020 (post-implementation). Non-parametric tests examined differences in service outcomes between the implementation periods. Results Pathway use varied widely across sites, ranging from 3.1% at site 4 to 83.0% at the lead site (site 2). More referrals to community MH agencies (p <.001) were made at discharge during post-implementation at the lead site compared to pre-implementation, and mixed results were obtained regarding whether clinicians’ risk assessments aligned with MH service recommendations. LOS significantly increased at the lead site (p <.001) and non-lead sites (sites 1, 3, 4; p =.02) between pre- and post-implementation. Revisits and admissions/transfers did not change significantly at any site. Conclusion Implementation was partially successful at the lead site, showing high pathway use and greater referrals to community MH agencies. These findings emphasize the complexity of implementing pathways in various ED settings. Successful implementation requires integration into existing workflows. Trial registration ClinicalTrials.gov (NCT02590302). Registered on 29 October 2015.